(untitled) (Archives of Mechanics - Test, 2012)
A literature review of liquid and gas flows in compliant tubes, ducts and cavities in living bodies is presented. The common features of such flows as determined by fluid–structure interactions and system instabilities are described. The corresponding mathematical models are given and theoretical and numerical results are discussed. Original new results on flow stabilization in layered viscoelastic tubes in biosystems are also presented.